108 Poor Appetite is Common in Hospitalised Older People and Associated with Subclinical Low Mood. (6th February 2020) - Cox, N J; Lim, S E R; Baylis, D; Howson, F; Sayer, A A; Robinson, S M; Roberts, H C
Abstract: Introduction: Appetite loss in older people -anorexia of ageing (AA) - is common. Recognised consequences include undernutrition, sarcopenia, frailty, and increased mortality after discharge from hospital. Identification and management of AA may prevent onset of these health burdens. Whilst appetite can be assessed, this is often not routine. Methods: Cross-sectional data from three studies (carried out 2010-2017), with comparable data collection methods and drawn from the same population, were combined. Participants were over 70 years, admitted to acute wards within a large UK hospital. Appetite was assessed using the simple 4 item Simplified Nutritional Appetite Questionnaire (SNAQ); a score of ≤14/20 defines poor appetite. Correlates of SNAQ scores were evaluated. Results: The dataset included 474 participants (64% female) with mean age 84 (6.5), median Barthel 78 (IQR 53-91), mini-mental state exam (MMSE) 27 (IQR 23-29) and comorbidity index 5 (IQR 4-7). The median GDS for the population was 4 (IQR 4-6). The mean SNAQ score was 13.9 (SD 2.6), and 265 (56%) participants scored ≤14 indicating poor appetite. There was no significant difference between mean SNAQ scores of men and women (P=.26), or those living alone and with others (P=.62). Age, MMSE, comorbidity index, and total number of medications were not related to SNAQ score in continuous analyses but geriatric depression score (GDS-15) was (adjusted coefficient -.248; P<.001); such that lower mood was associated with poorer appetite. Conclusions: These findings highlight the importance of assessing appetite in hospitalised older people, as poor appetite is very common. Appetite can be assessed in hospital using the simple 4 item SNAQ tool. Subclinical low mood, measured by GDS-15, had the strongest association with SNAQ score whilst in hospital. Therefore, for those with poor appetite in hospital, clinicians should have a low threshold to evaluate and treat low mood.